The Road Traffic Modelling and Design of the Traffic Database of Győr in Project Smarter Transport - Fazekas, S.; Péter, T. (Acta Technica Jaurinensis, 2013)
In this paper we review our tasks in project Smarter Transport, and overview the network modelization process of city Győr. We also review the main concepts of the traffic road network databank, which will store the measured and assessed quantities and the road network model. We discuss the goals and the main requirements of the database system, which aims to support the modelling process. We briefly overview the architecture.